Late-Onset 22q11.2 Deletion Syndrome With Mild Cardiac Phenotype: A Unique Adult Presentation Diagnosed at 45 Years of Age - Elizondo Plazas, Anasofia; López Uriarte, Graciela Areli; González González, José Gerardo; Rodríguez Gutiérrez, René; Martínez Villarreal, Laura Esther; Treviño Juárez, Ángel Sebastián; González Velázquez, Camilo Daniel (2023)
This case report presents a detailed exploration of an adult-onset 22q11 deletion syndrome, a rare genetic disorder typically diagnosed in children. The report highlights the diagnostic challenges posed by this atypical presentation, emphasizing the need for clinicians to consider such conditions in differential diagnoses, especially in adults. This case is remarkable for its late onset and mild symptoms, which significantly deviated from the common pediatric presentation, including hypocalcemia due to hypoparathyroidism and a fenestrated atrial septal defect without significant hemodynamic implications. The importance of recognizing the broad phenotypic variability of the syndrome and the implications for clinical practice are discussed, providing insights into the genetic and phenotypic diversity of the condition. In conclusion, this case illuminates the diverse clinical spectrum of adult-onset 22q11 deletion syndrome, emphasizing its relevance to clinical practice.